Not All Determinants Are Equal: A Systematic Literature Review of Education, Employment Status, and Household Size in Household Extreme Poverty - Yusuf Husain; Agus Suman; Dias Satria (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Extreme poverty remains an urgent global development challenge. Determinants such as education, employment status, and household size are often studied in isolation, fragmenting understanding of their interactions, while findings are inconsistent, particularly for household size and informal employment, motivating this review. This study synthesizes empirical evidence on how educational attainment, employment status, and household size affect the probability of household extreme poverty, identifying patterns of consistency and inconsistency across prior studies. Following PRISMA guidelines, this Systematic Literature Review searched Scopus using a Boolean string combining keywords for education, employment status, household size, and extreme poverty. Studies were selected via inclusion and exclusion criteria on year, language, type, and relevance; extraction was narrative, without formal quality assessment. Twelve studies support a negative education effect, though two report non-significant or reversed results. Eight studies link unstable employment to higher poverty risk, but only two directly test the formal-informal dichotomy. Nine studies agree that a larger household size raises poverty risk, though the magnitude varies up to sevenfold. Education and household size offer the most consistent evidence as determinants, while employment status needs further direct testing given reliance on non-equivalent proxies. Future research should integrate all three determinants into a single model and apply meta-analysis to test the identified magnitude gaps.